Understanding Students’ Motivation Factors in Learning Science as the Way to Nourish Elementary School Teacher’s Creativities in Teaching Science - Lily Barlia (Program Studi PGSD Kampus UPI di Serang, 2016)
This study investigated motivational factors that are related to elementary school students’ in learning science. While previous studies have recognized the resistance of students’ scientific conception to change because of lack of motivation to learn. Few have investigated the role that non-cognitive factors might play when students are exposed to science instruction. Two research questions were examined: [a] whatinstructional strategies did the teacher use to increase students’ motivation to learn science? [b] What individual elementary school student profiles can be constructed from the four motivation factors [i.e., goals, values, self-efficacy, and control beliefs] and how are these profiles linked to elementary school student engagement [i.e., behavioral and cognitive engagement] in learning of science? Eleven fourth grade students and the teacher of the public schools in Cilegon District, Banten, were selected. Data collection for this study included student’s self-reported responses to the Motivated Strategies for Learning Questionnaire [MSLQ] that are translated to Bahasa Indonesia and modified to the fourth grade students developmentally appropriate, classroom observation of students and teacher, and structured interviews. Analysis of these data resulted in a motivational factors for each student and cross case analysis for entire group. Results from this study indicate that each student has different motivation factors that are mostly influenced to students’ engagement in learning science. Among these motivation factors, task value and control beliefs were the most important for students to engage in learning science. Furthermore, for most of students included in this study, their motivation to learn science was also influenced by other factors that are not directly related to the four motivational factors assessed by the MSLQ, these factors included: [a] preparation for the next education [Junior high school and beyond] as well as future career, [b] personal interests to learn science, and [c] the course [science] is required for graduation. The implications of these findings are that the teachers need to create teaching learning strategies that can encourage students to develop learning strategies for understanding of science contents. The conclusions drawn from this study are that the elementary school teachers have to be aware of the importance of student’ motivation factors to learn science in order to develop his/her creativity in conducting of science teaching and learning process in elementary school.